(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This study examined the relationship between organisational learning and sustainability in the telecommunication industry in Nigeria. The study adopted a descriptive survey research design while the population of the study were employees of 8 telecommunication companies operating in the Port Harcourt business district of Rivers State, Nigeria. With a sample size of 155 employees of the companies studied, the primary data was generated with a well-structured questionnaire using purposeful sampling method. Statistical analysis with Pearson Correlation analysis showed that the two dimensions of organisational learning (individual learning and collaborative learning) had positive and significant relationship with the two measures of sustainability(economic performance and social responsibility). The study concluded that individual learning and collaborative learning constitute important determinants of business sustainability in the telecommunication industry. It was recommended that companies should pay attention to the factors that are capable of influencing their employees to think and ack sustainably in the workplace.